Marketing management - Kotler, Philip; Keller, Kevin Lane, 1956-; Chernev, Alexander; Sheth, Jagdish N.; Shainesh, G. (Hoboken, NJ : Pearson Education, 2022)
"The 16th edition of Marketing Management builds on the classic examples, core concepts, and logical structure that made the first edition a landmark text. Much has changed since the 15th edition was published. Ongoing globalization; the increasing role of corporate social responsibility; advances in technology, e-commerce, and digital communication; the growing impact of social media, and the widespread use of data analytics, marketing automation, and artificial intelligence have disrupted many industries and have opened doors to new business models. Responding to these changes, the 16th edition was redesigned from the ground up to provide managers with the tools necessary to succeed in the new market environment. The 16th edition builds on the fundamental strengths of past editions that distinguish Marketing Management from all other marketing management texts: - Managerial orientation. The book focuses on the major decisions that marketing managers and top management face in their efforts to harmonize the organization's objectives, capabilities, and resources with marketplace needs and opportunities. - Analytical approach. The text presents conceptual tools and frameworks for analyzing recurring problems in marketing management. Cases and examples illustrate effective marketing principles, strategies, and practices. - Multidisciplinary perspective. Marketing Management draws on the rich findings of various scientific disciplines-such as economics, behavioral science, and management theory-for fundamental concepts and tools that are directly applicable to marketing challenges. - Universal applications. The book applies strategic thinking to the complete spectrum of marketing: products, services, persons, places, information, ideas, and causes; consumer and business markets; profit and nonprofit organizations; domestic and foreign companies; small and large firms; manufacturing and intermediary businesses; and low- and high-tech industries. - Comprehensive and balanced coverage. Marketing Management covers the topics a manager must understand in order to design and execute a successful marketing campaign"--
Includes bibliographical references and index.
BBS
TANIA AKTER (PIN3153)
Lecturer, BBS
(Lost Marketing management, Fifteenth edition, Accession no.3010031148 and replaced by Latest one Sixteenth edition.)
Keywords: Marketing -- Management; Business & finance; Management